KINERJA ANGGARAN SEKTOR PUBLIK BERDASARKAN AKUNTABILITAS, PARTISIPASI, PENGAWASAN, DAN KOMITMEN ORGANISASI - Hawa, Putri; Fitriasuri, Fitriasuri (Universitas Muhammadiyah Palembang, 2024)
The purpose of this study was to test and analyze the relationship between the influence of accountability, participation and supervision on the performance of the value for money concept budget and organizational commitment as a moderating variable. This study used a quantitative method whose population was employees/staff at the PSDA Office of South Sumatra Province totaling 32 respondents. The data analysis method in this study was quantitative analysis with the analysis technique used, namely Moderated Regression Analysis (MRA) SPSS software version 26. The results showed that accountability and participation had a positive and significant effect while supervision did not affect the performance of the value for money concept budget. While Participation had a negative and significant effect and supervision had a positive and significant effect on the performance of the value for money concept budget moderated by organizational commitment and organizational commitment could not moderate accountability on the performance of the value for money concept budget at the PSDA on duty South Sumatra Province.